Universe - Freedman, William J.; Kaufmann, William J. (W.H. Freeman and Company, 2008)
Known edition after edition for its state-of-the-science coverage, Universe breaks new ground in its Eighth Edition with added pedagogical support and pioneering media and supplements. It places the basics of astronomy and the process of science within the grasp of introductory students